Development of the Barokah Mushroom House Business in South Rabangodu Village: Pengembangan Usaha Rumah Jamur Barokah di Kelurahan Rabangodu Selatan - Ernawati, Sri Ernawati; Ismunandar, Ismunandar; Riandi, M. Inas; Zaaria, Ainun Zaaria; Purnamasari, Defis Purnamasari (CONSEN: Indonesian Journal of Community Services and Engagement, 2024)
PMP (Beginner Community Service) activities carried out with partners targeting the barokah mushroom house business in South Rabangodu Village, Bima City. The problem with the barokah mushroom house business is that the number of Baglogs is still small, they have not implemented promotions through digital marketing, they don't have attractive packaging and they don't have a business logo and they don't have a job description. Therefore, concrete steps are needed regarding socialization related to increasing production capacity through the use of production equipment such as mixing machines and baglog press machines, training in the application of digital marketing for business promotion activities, training and support regarding the importance of applying logos and packaging, so that products can be more attractive to consumers, expanding business reach, and supporting increased sales and creating job description documents for mushroom house businesses. This community service uses planning, implementation and evaluation methods. The results of the training and socialization carried out where the pre-test showed that participants did not understand and understand the importance of digital marketing and attractive packaging and logo creation, while the results of the post-test carried out showed that participants already understood the importance of promotion using digital marketing with reels which is currently trending. and packaging to increase the selling power and competitiveness of products and be able to create logos using the Canva application